MUHADHOROH SEBAGAI MEDIA PENGEMBANGAN DAN KEPERCAYAAN DIRI SANTRI DI PONDOK PESANTREN IRSYADUL IBAD KECAMATAN PEMAYUNG KABUPATEN BATANGHARI PROVINSI JAMBI - Ramadon, Pebri; Jamilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of public speaking skills and the confidence of students as provisions for community life. This study aims to describe the implementation, supporting and inhibiting factors of the muhadhoroh activities in developing the speaking skills and self-confidence of the students. This research uses a qualitative method with a descriptive approach. Data were collected using triangulation techniques, which involved combining several data collection methods, namely observation, interviews, and documentation. The research results show that the muhadhoroh activities are conducted regularly every Thursday nite thru the stages of planning, implementation, and evaluation. This muhadhoroh activity can develop the students' self-confidence in speaking in public. Supporting factors include active guidance from the ustadz and structured practice sessions, while hindering factors encompass the lack of preparation among students, the low interest of some students, and limited facilities. Based on the research results, the researcher can conclude that the muhadhoroh activity is very significant in increasing the students' confidence in public speaking.